The Influence of MSME Perfomance Seen from Innovation as Mediation - Lusy; Hermanto, Yustinus Budi; Boedihardjo, Damianus Christian (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2025)
This study examines the effect of Intellectual Capital and entrepreneurial Orientation on Company Value, especially MSMES with Innovation as a mediating variable. This study used a quantitative approach with questionnaires distributed to 237 respondents, varied, as many as 182 respondents had micro-businesses, while 55 respondents had small businesses. Data were processed using SEM analysis, with AMOS 24 software. The results showed that Intellectual Capital and Entrepreneurial Orientation affected Innovation. However, Intellectual Capital and Innovation do not affect Company Value. Besides that, Entrepreneurial Orientation influences the Company’s Value. Another hypothesis shows that Innovation does not mediate Intellectual Capital on Company Value, but mediates Entrepreneurial orientation on Firm Value. The novelty of this research lies in the model created. As for future development, it can be more detailed to distinguish Innovation, both from products and innovation from the process.